2021
DOI: 10.22603/ssrr.2020-0195
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Spontaneous Restoration of Lumbar Lordosis after Single-Level Transforaminal Lumbar Interbody Fusion for Degenerative Lumbar Diseases

Abstract: Introduction Preoperative factors that predict postoperative restoration of lumbar lordosis (LL) are not well understood. To investigate whether preoperative postural correction of LL, sagittal malalignment, or lumbar flexibility are associated with the postoperative restoration of LL in patients treated with a single-level transforaminal lumbar interbody fusion (TLIF), a retrospective cohort study was conducted. Methods We enrolled 104 patients (mean age: 67.5±10.7 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A favorable surgical outcome of single-level anterior fusion was reported in patients with thoracolumbar burst fracture in which the cranial endplate is mainly involved and the caudal endplate has no or slight injury. [ 12 , 15 , 21 ] A previous study showed that postoperative correction loss was not significantly different between single-level and two-level anterior fusion surgery in such patients. [ 17 ] Miyakoshi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A favorable surgical outcome of single-level anterior fusion was reported in patients with thoracolumbar burst fracture in which the cranial endplate is mainly involved and the caudal endplate has no or slight injury. [ 12 , 15 , 21 ] A previous study showed that postoperative correction loss was not significantly different between single-level and two-level anterior fusion surgery in such patients. [ 17 ] Miyakoshi et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 , 18 ] More recently, preoperative difference in lumbar lordosis between standing and supine positions (DiLL) was proposed as a predictive factor for postoperative lumbar alignment changes after lumbar surgery for lumbar degenerative disease. [ 3 , 13 , 15 ] From our experience, it is suggested that postural differences in LKA are useful for evaluating the stability of thoracolumbar fractures after fusion surgery and predicting postoperative loss of correction.…”
Section: Discussionmentioning
confidence: 99%